Keefektifan Modul Berbasis Guided Inquiry dilengkapi Komik terhadap Kemampuan Berargumentasi ditinjau dari Minat Baca Siswa - Puji Hendarto; Maridi Maridi; Baskoro Adi Prayitno (Graduate School of Universitas Negeri Malang, 2018)
Abstract: This research aims to examine the effectiveness of Guided Inquiry-Based Modules Supplied with Comics on The Subject Matter of Human Digestive System to Improve the Argumentation Skills of the students with high and low reading motivation. The used method was a quasi-experiment with 2x2 factorial design. The researcher used an intact group technique to determine the sample. The sample was divided into two groups, namely the control group and the experimental group. In addition, each sample groups were divided into two groups of high reading motivation and low reading motivation. The instrument used to obtain the data of argumentation skill was an essay test based on the indicators of Argumentation Skills. The instrument of reading motivation used the Motivations for Reading Questionnaire (MRQ). Data Analysis using ANCOVA test with a significance level of <0.05. The results of the data analysis showed the Guided Inquiry-Based Modules Supplied with Comics on the Subject Matter of Human Digestive System effective toward students’ Argumentation Skills.Abstrak: Penelitian ini bertujuan untuk menguji efektivitas modul berbasis guided inquiry pada materi sistem pencernaan manusia dilengkapi komik untuk meningkatkan kemampuan berargumentasi siswa dengan minat baca tinggi dan rendah. Metode yang digunakan adalah kuasi eksperimen dengan desain faktorial 2x2. Peneliti menggunakan teknik intact group untuk menentukan sampel. Sampel dibagi menjadi dua kelompok, yaitu kelompok kontrol dan kelompok eksperimen. Selain itu, masing-masing kelompok sampel dibagi menjadi dua kelompok minat baca tinggi dan minat baca rendah. Instrumen yang digunakan untuk memperoleh data kemampuan berargumentasi adalah tes esai berdasarkan indikator kemampuan berargumentasi. Instrumen minat baca menggunakan Motivations for Reading Questionnaire (MRQ). Analisis data menggunakan uji anakova dengan tingkat signifikansi <0,05. Hasil analisis data menunjukkan modul berbasis guided inquiry dilengkapi komik pada materi sistem pencernaan manusia efektif terhadap kemampuan berargumentasi siswa.